(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The article raises the question of the importance and necessity of innovation and innovation in the learning process, how these innovations solve problems in education and what they bring to the discipline. The very concept of “innovation in education” is being explored, so there is no consensus on this matter among scientists yet. It also raises the question of the importance and necessity of innovations and innovations in the learning process. How these innovations solve problems in education and what they bring to the disciplines. The question of the importance of the teaching profession in the modern information society is considered. By innovating in the training department, the company is committed to developing the best teaching and learning strategies in schools and colleges.